Shall We Dance? Defining Sexuality and Controlling the Body in Contemporary Indonesia - Madasari, Okky (Religions, 2021)
This article examines how Indonesia, the world’s third-largest democracy, came to define sexuality for its general population once intimacy was brought into the public sphere. However, its Islamic version had predominantly been based on interpretations pushed by politically hardline Islamist groups. The influence of this lobby (to be referred to as belonging to the stream of ‘conservative Islam’) grew steadily after the downfall of the Suharto regime in 1998 and culminated in the passage of an antipornography law ten years later. Focusing on the definitions of sexuality and pornography forwarded by these groups, this article analyses their limitations as well as the power contestations behind the passage of the antipornography legislation. It argues that such narrow interpretations of sexuality have had a marked impact on the nation, in particular the curtailment of its popular culture and creative industry. This has resulted in the arbitrary persecution and banning of cultural products considered to violate Islamic morality and propriety. The condemnation of dangdut singer Inul Daratista, and her ‘drill dance’, is one of many examples of such suppression.